Enhancing Regional Power Trade in Central Asia - World Bank (World Bank, Washington, DC, 2017)
In response to a request from Central Asian (CA) countries at the CAREC Energy Sector Coordination Committee meeting, held in March 2015 in Ulaanbaatar, Mongolia, the World Bank commissioned a study to estimate unrealized benefits from regional power trade for the four Central Asian countries of Kazakhstan, Kyrgyzstan, Tajikistan, and Uzbekistan during the period from 2010 – 2014. The study was implemented by AF Mercados from October 2015 through June 2016. This report reviews the key findings of the AF Mercados Report, with further details to be found in the Report itself. The analysis was focused on power trade benefits aggregated at the regional level, as well as country-specific benefits. Three cases were considered, namely (i) benefits including fuel savings only at historic energy prices, (ii) benefits including both fuel savings and economic value of avoiding unserved energy at historic fuel prices, and (iii) benefits including fuel savings and the economic value of avoiding unserved energy with fuel costs estimated to be at “market” energy prices. The findings of the report, show that the benefits for the region could have amounted to nearly USD1.5 billion if only fuel savings were taken into account. Should economic value of avoiding unserved power demand be added to benefits, the benefits would have reached almost USD5.2 billion for historic energy prices and about USD6.4 billion for market energy prices. It’s worth noting that each country could also have benefited in any of the cases, except for Kyrgyzstan for the case of including fuel savings only. Furthermore, if the countries operated together, they could also save over USD 80 million annually, or USD 400 million during the period from 2010 -2014, by sharing the regional hydro resources to provide operating reserves, instead of purchasing reserves at current market prices from outside sources.